Manifesto Pendidikan Islam Moderat: Rekonstruksi Paradigma Pendidikan Berbasis Wasathiyah - Asyari Abdul Wafa (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study reconstructs the paradigm of moderate Islamic education based on wasathiyah through a qualitative library research approach with a philosophical-critical orientation. The findings reveal that moderate Islamic education represents an integrative educational framework that balances rational, spiritual, and ethical dimensions within a coherent epistemological structure. The Qur’an and Hadith function not only as primary theological sources but also as normative foundations that guide inclusive, tolerant, and adaptive educational practices. The educational objectives emphasize the harmonization of intellectual, emotional, and spiritual intelligence to cultivate individuals with reflective awareness and moral integrity. Core characteristics such as tawassuth (moderation), tasamuh (tolerance), tawazun (balance), i’tidal (justice), musawah (equality), and shura (deliberation) serve as operational principles in shaping socially cohesive and non-extremist educational environments. Furthermore, the implementation of diverse and context-sensitive pedagogical methods strengthens the internalization of moderate values. This study underscores that wasathiyah-based Islamic education provides a strategic framework for fostering a peaceful, pluralistic, and ethically grounded society in contemporary global contexts.